2019
DOI: 10.1002/ep.13248
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and estimation of densities of different biodiesel–diesel–alcohol ternary blends

Abstract: Density is one of the most important fuel properties influencing the injection, spray, and combustion characteristics. Since a number of articles have recently been performed investigating the effects of biodiesel–diesel–alcohol ternary blends on combustion characteristics and exhaust emissions, the reliable density data and regression models for the ternary blends become more important in developing accurate spray, combustion and emission models. However, there is lack of studies which focus on (a) the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The average absolute relative deviations were lower than 2.37%. Gülüm et al [46] developed an artificial neural network (ANN) predictive model for the density of ternary fuel blends (diesel-biodiesel-alcohols (methanol, ethanol, and isopropanol)), which outperformed exponential and linear regression models.…”
Section: Introductionmentioning
confidence: 99%
“…The average absolute relative deviations were lower than 2.37%. Gülüm et al [46] developed an artificial neural network (ANN) predictive model for the density of ternary fuel blends (diesel-biodiesel-alcohols (methanol, ethanol, and isopropanol)), which outperformed exponential and linear regression models.…”
Section: Introductionmentioning
confidence: 99%
“…Atmanli et al 41 reported that n‐butanol improved the blending miscibility between diesel and raw cotton oil. In another study, Gulum et al 42 estimated the density of diesel/ waste cooking oil biodiesel/alcohol ternary blends using artificial neural networks and exponential model. They provided a reliable predictive model of density data of diesel/waste cooking oil biodiesel/alcohol ternary blends to facilitate spray and combustion studies of ternary blends.…”
Section: Introductionmentioning
confidence: 99%